Statistical Optimization of Lactic Acid Production by Lactobacillus pentosus using Hemicellulosic Hydrolysate from Sugarcane Bagasse - Wischral, Daiana (2018)
Lactic acid, traditionally obtained through fermentation processes, presents numerous applications in the chemical industry. Among these is the production of polymers, more specifically biodegradable polylactic acid (PLA). Development of processes that use low cost substrates, such as bioproduction of lactic acid, could improve the economic viability of bioprocesses. Thus, the present work reports investigation of hemicellulose hydrolysate from sugarcane bagasse as a sole carbon source for lactic acid production by Lactobacillus pentosus ATCC 8041. Initially, sugarcane bagasse was pretreated with acid in a solid:liquid ratio of 1:2.8 (1 g of bagasse: 2.8 mL of sulfuric acid solution 1 % v/v) and at a temperature of 121°C for 27 minutes. Then, concentration of both the hemicellulose hydrolysate and the yeast extract in MRS medium were optimized usingResponse Surface Methodology through software STATISTICA 6.0. Once the optimal conditions (40 % of hemicellulose hydrolysate and 5 g/L of yeast extract) were validated, fermentations were carried out in anaerobic conditions at 37°C and 120 rpm. After 48h, 19.17 g/L of lactic acid were produced, corresponding to a volumetric productivity of 0.40 g/L.h1. Findings of this work demonstrate that hemicellulose hydrolysate from sugarcane bagasse is a promising carbon source for lactic acid production.